GERMINATION AND RE-INDUCTION OF DISSECATION TOLERANCE IN SEEDS OF Senna multijuga (RICH.) IRWIN ET BARN - Ribeiro, Diego Egidio; Alvarenga, Amauri Alves de; Martins, Joeferson Reis; Rodrigues, Amanda Cristiane; Maia, Vitor Oliveira [UNESP] (Centro Pesquisas Florestais, Ufsm, 2016)
The aims of this study were to verify the effects of different tests in the overcoming dormancy, excellent germination terms, as light and temperature, and the possibility of re-induction of desiccation tolerance in Senna multijuga seeds. We evaluated two tests for overcoming dormancy: immersion in water with an initial temperature of 100 degrees C (hot water) and immersion in water at a constant temperature at 100 degrees C for 20 seconds boiling water), both treatments followed by rest out of the heating for 24 hours. For the germination test, we evaluated 25 degrees C, 30 degrees C (constant) and 20-30 degrees C (alternate), in the presence and absence of light. For the reinduction of desiccation tolerance, we selected seeds germinated with 1, 2, 3 and 4mm of radicle length. We submitted the germinated seeds to the follow treatments: no incubation, incubation in polyethylene glycol (PEG6000) at the -1,4, -1,7 and -2,0MPa; incubation in PEG -1,4MPa + ABA at the concentrations of 1, 10 and 100 mu M. The tests followed a completely randomized design (DIC) using 4 repetitions of 25 seeds. The overcoming dormancy using hot water provided the best germination (65%). The Senna multijuga seeds are not photoblastic required, but in light conditions the germination was higher. We observed the resumption of the radicle growth in germinated seeds of up to 3mm length.
Keywords: light; tegumentar dormancy; canafistula